2010
DOI: 10.1002/ijc.25538
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of cancer growth by histone demethylases

Abstract: Cancer is traditionally viewed as a primarily genetic disorder. However, it is now increasingly apparent that epigenetic abnormalities play a fundamental role in cancer development. Aberrant expression of histone-modifying enzymes has been implicated in the course of tumor initiation and progression. The discovery of a large number of histone demethylases suggests an important role for dynamic regulation of histone methylation in biological processes. The observation that overexpression, amplification or mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…Although the molecular mechanisms underlying prostate cancer progression to lethal hormone refractory prostate cancer (HRPC) [9][10][11][12][13] are incompletely understood, activation of downstream signals by hypersensitive or overexpressed ARs is considered to be important. The epigenetic status of prostate cancer cells is modulated by AR binding and the subsequent recruitment of co-activators or co-repressors [14][15][16][17][18] . Acetylation, methylation, phosphorylation, ubiquitylation and ADP ribosylation of histones critically affect transcriptional regulation by ARs [19][20][21] .…”
mentioning
confidence: 99%
“…Although the molecular mechanisms underlying prostate cancer progression to lethal hormone refractory prostate cancer (HRPC) [9][10][11][12][13] are incompletely understood, activation of downstream signals by hypersensitive or overexpressed ARs is considered to be important. The epigenetic status of prostate cancer cells is modulated by AR binding and the subsequent recruitment of co-activators or co-repressors [14][15][16][17][18] . Acetylation, methylation, phosphorylation, ubiquitylation and ADP ribosylation of histones critically affect transcriptional regulation by ARs [19][20][21] .…”
mentioning
confidence: 99%
“…Indeed, misregulation of tumor suppressor genes and oncogenes by histone methyltransferases and demethylases has been shown to associate with various human cancers (42,43). For example, PLU1/JARID1B is overexpressed in breast, prostate, and lung cancers (40,41,44,45) and is involved in silencing tumor suppressor genes such as 14-3-3-s, CAV1, HOXA5, and BRCA1 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of SIRT1 expression was not associated with hypermethylation of the gene promoter region (supplemental Figure 4A-D). Furthermore, chromatin immunoprecipitation followed by quantitative PCR revealed that the "active" marks trimethyl-H3K4 (H3K4me3) associated with the SIRT1 promoter were significantly decreased in PT-ECFCs compared to CT-ECFCs, whereas the repressive marks trimethyl-H3K9, associated with heterochromatin formation, 23 was increased (supplemental Figure 4E). These results demonstrate that SIRT1 repression in PT depends at least in part, on a loss of "active" epigenetic marks at its promoter.…”
Section: Pt-ecfc Senescence Is Associated With Changes In Sirt1 Exprementioning
confidence: 99%